Satria Darma MEKANISME PASAR DALAM ISLAM; TELAAH KAJIAN EKONOMI MIKRO SYARIAH - Satria Darma (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2022)
AbstractThis study aims to analyze how the market mechanism is in accordancewith Islamic economics. This research uses exploratory study method,descriptive analysis in analyzing secondary data related to these problems.The results show that in the market mechanism in Islam, sharia values mustbe grown, such as justice, openness, honesty and fair competition, which areuniversal values. To ensure that these values are implemented, the role of thegovernment is needed, as exemplified during the time of the Prophet andthereafter, which guided Islamic law. Keywords: mechanisms, markets, microeconomics, Islamic economics,Islam.